2022
DOI: 10.3389/fimmu.2022.925702
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation Inhibition Causes Impaired Mouse Embryo Quality and Blastocyst Hatching Failure Through Elevated Oxidative Stress and Reduced IL-1β

Abstract: Mammalian blastocyst hatching is an essential prerequisite for successful embryo implantation. As the rate-limiting step of current assisted reproductive technology, understanding the key factors regulating blastocyst hatching would be significantly helpful to improve the performance of the assisted reproductive practice. In early embryo development, the fine-tuned elimination of maternal materials and the balanced protein turnover are inevitable for the competent to hatch and implant into endometrium. Neddyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies have used blastocyst diameter and total cell number to assess blastocyst quality, 29,30 and oxidative stress is also an indicator of blastocyst quality 31,32 ; therefore, these parameters were examined to determine blastocyst quality. Studies have shown that blastocyst quality is critical for embryonic stem cell production and other related applications 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used blastocyst diameter and total cell number to assess blastocyst quality, 29,30 and oxidative stress is also an indicator of blastocyst quality 31,32 ; therefore, these parameters were examined to determine blastocyst quality. Studies have shown that blastocyst quality is critical for embryonic stem cell production and other related applications 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of this pathway in bovine embryos will lead to delayed embryonic development and reduced blastocyst formation rate [12]. In our earlier research, we discovered that neddylation suppression results in poorer mouse embryo quality and unsuccessful blastocyst hatching [13]. Nonetheless, the detailed molecular mechanism of neddylation governing embryonic development has not yet been understood.…”
Section: Introductionmentioning
confidence: 99%